Restructuring the Governance of PUSSAKO FH-UHO: Building a Progressive, Accountable, and Innovative Research Institution - Risman Setiawan (Universitas Dehasen Bengkulu, 2026)
Limited access to justice and suboptimal governance of legal research institutions at universities often hinder the fulfillment of the public’s constitutional rights, particularly in addressing critical issues in Kendari City such as agrarian conflicts and low legal literacy. This community service initiative aims to reconstruct the governance of PUSSAKO FH-UHO to transform it into a progressive, accountable, and innovative research institution. The method employed is Participatory Organizational Empowerment, which includes stages of internal audit, Focus Group Discussions, and capacity-building workshops based on a progressive legal paradigm. The results of the community service initiative demonstrate significant transformation in the organizational structure, which is now more responsive and accountable in addressing legal issues in Kendari City. Key findings include the institution’s success in drafting a policy on land data protection, as well as the enhancement of advocacy and constitutional literacy programs for marginalized communities. This demonstrates that strengthening the internal governance of the study center can bridge the gap between formal regulations and the community’s need for substantive justice. In conclusion, the restructuring of PUSSAKO FH-UHO’s governance has strategic implications for public policy practices through the provision of more inclusive legal recommendations and the strengthening of access to social justice. Transformative research institutions play a vital role as driving forces in realizing a progressive, independent, and sustainable legal culture in the Southeast Sulawesi region.